High‐Precision Sr‐Nd‐Hf‐Pb Isotopic Composition of Chinese Geological Standard Glass Reference Materials CGSG‐1, CGSG‐2, CGSG‐4 and CGSG‐5 by MC‐ICP‐MS and TIMS. Issue 3 (22nd May 2020) - Yang, Yue‐Heng; Yang, Ming; Jochum, Klaus Peter; Wu, Shi‐Tou; Zhao, Han; Xie, Lie‐Wen; Huang, Chao; Zhan, Xiu‐Chun; Yang, Jin‐Hui; Wu, Fu‐Yuan
Abstract : To assess the homogeneity of and provide the first Sr‐Nd‐Hf‐Pb isotopic reference values for the Chinese Geological Standard Glasses CGSG‐1, CGSG‐2, CGSG‐4 and CGSG‐5, we measured these isotopes in several measurement sessions over the course of nearly 3 years. The results were obtained by high‐precision MC‐ICP‐MS and TIMS. Our investigation indicates that these CGSG glass reference materials are homogenous with regard to Sr‐Nd‐Hf‐Pb isotopic distribution and are therefore suitable geochemical materials for Sr‐Nd‐Hf‐Pb isotope measurements. Clear differences in Sr‐Nd‐Hf‐Pb isotopic composition were observed between the glasses and the original powdered rock reference materials (CGSG‐2 and GSR‐7, and especially CGSG‐5 and GSR‐2) because of flux addition during preparation of the glasses. The new Sr‐Nd‐Hf‐Pb isotope data provided here might be useful to the geochemical community for in situ and bulk analysis. Key Points: High‐precision Sr‐Nd‐Hf‐Pb isotopic compositions of CGSG‐1, CGSG‐2, CGSG‐4 and CGSG‐5 are provided. CGSG are homogenous with regard to Sr‐Nd‐Hf‐Pb isotopic distribution and suitable geochemical materials for measurement of these isotopes. Clear difference in Sr‐Nd‐Hf‐Pb isotopic composition was observed between the glasses and the original powdered rock reference materials.